Potential of Trichoderma strains to positively modulate plant growth processes and bulb yield in Rabi onion - Dutta, Ram; Kumar, Satish; Jayalakshmi, K.; Radhakrishna, A.; Bhagat, Kiran; Manjunatha Gowda, D. C.; Karuppaiah, V.; Bhandari, Hem Raj; Bomble, Ram; Gurav, Vishal; Mahajan, Vijay; Singh, Major (Frontiers in Sustainable Food Systems, 2024)
The use of beneficial microbes is hitherto known and constantly increasing in agriculture due to their positive impact on crop growth and yield, and their minimal negative impact on the environment. The objective of this study was to evaluate the impact of eight Trichoderma strains of diverse origin on crop growth and yield of onion under field conditions. The identity of the strains used in the current study was confirmed by ITS and Tef1 gene sequencing. Field experiments were conducted in the Rabi season for 2 years (2020–21, and 2022–23) to evaluate the effect of the application of eight different Trichoderma strains that were applied individually and separately as eight different treatments (T1–T8) in experimental plots. In the plant growth promotion assay conducted in vitro, all strains showed the ability to produce IAA (indole-3-acetic acid), with levels ranging from 23.52 μg/mL (T6) to 45.54 μg/mL (T3). Our results revealed that Trichoderma treated experimental plots displayed better growth indices (plant height, pseudostem diameter), RWC (Relative water content), leaf chlorophyll content, and yield-attributing features like biomass (bulb and root dry mass), bulb diameter, and harvested bulb yield compared to the untreated control plants. In terms of yield, the T2 strain exhibited the highest bulb yield consistently for both the years (2020–21 and 2022–23) followed by T3 being statistically at par with T5. Among all the evaluated Trichoderma strains, the strain T2 (OGRDT2) and T3 (GRDT1), taxonomically identified as Trichoderma longibrachiatum, registered bulb yield of 32.24 t/ha and 30.76 t/ha, respectively while T5 (GRDT3), identified as Trichoderma asperellum, registered 30.55 t/ha average yield for 2 years compared to 24.08 t/ha average yield recorded for untreated control plants with an increase of 34, 28 and 27%, respectively. Based on our findings, it is concluded that the T. longibrachiatum strains OGRDT2 (T2) and GRDT1 (T3), T. asperellum strain GRDT3 (T5) are the best inducers of the onion crop growth and yield in the Rabi season and would be explored further for its commercial application in onion farming.